TEKNOLOGI HOLOGRAM UNTUK E-LEARNING BAHASA ARAB PRA-SD DAN SEKOLAH DASAR - Ismail Noor Hassan; Nurmida Catherine Sitompul; Nunung Nurjati (Akademika : Jurnal Teknologi Pendidikan, 2021)
The objective of this study was to find the starting grade class in pre-primary and early primary school that adjustable with e-learning hologram technology for e-learning Arabic language. This experimental design research used a mixed, quantitative method for a score of control groups- traditional learning and experimental groups-hologram e-learning of primary school, a qualitative method for descriptive assessment reports, interview, and observation of pre-primary school. for group A the instrument's data are taken from the content of LKS which has explained the detail in the previous paragraph and the group B from the hologram movie that contains the content of LKS by considering the time span of learning between 10-20 minutes, the content of Arabic learning must emphasis in writing and pronouncing and the exception for the pre-primaryschool as the writing is not compulsory yet. The population of 68 participants. The validation quantitative data were analyzed t-test and else Mann–Whitney test, meta-analysis to describe result for the conclusion. The qualitative used triangulation of descriptive data for validation. The result shows that 1st grade, the sig. result 1.00 > 0.05 and 2sc of primary school, the sig. result 0.843 > 0.05 with hologram are indicating no significant gap with traditional learning, same effectiveness, but for pre-primary school with hologram is less-classical completeness 52.5% < 85%. The conclusion of this research is that hologram technology can be used for e-learning Arabic language subject that is adjustable for primary school starting 1st and 2sc grade.